Menjelajah Kultur Majapahit, Mencari Ã¢â‚¬Å“IdentitasÃ¢â‚¬Â Seni Rupa Kontemporer Jawa Timur - Bramantijo, Bramantijo (Jurnal Budaya Nusantara, 2017)
The identity of Indonesian art is loaded with political contents in the interests of harmony. Indentity becomesthe differentiator and positioning in artwords. East Java gets the fortunes to be the locus of Majapahit and heritage ofthe Majapahit culture, but the atmosphere of contemporary art gives artists of freedom to explore the variety oftraditional cultures in various loci and make as identity. The sole recognition of a culture by a group community is nolonger relevant. The other way, it occurs the ability of artists to discover the characteristics of traditional cultures and topresent it typically as a differentiator with other artists.